Isoliquiritigenin Attenuates Monocrotaline-Induced Pulmonary Hypertension via Inhibition of the Inflammatory Response and PASMCs Proliferation. (26th May 2019) - Jin, Haifeng; Jiang, Yang; Du, Fengxia; Guo, Linna; Wang, Guan; Kim, Sang Chan; Lee, Chul Won; Shen, Lei; Zhao, Rongjie
Abstract : Pulmonary hypertension (PH) is a progressive and serious disease, where exacerbated inflammatory response plays a critical role. Isoliquiritigenin (ISL), an important flavonoid isolated from Glycyrrhizae radix, exhibits a wide range of pharmacological actions including anti-inflammation. Previously we found ISL alleviated hypoxia-induced PH; in the present study, to extend this, we evaluated the effects of ISL on monocrotaline (MCT)-induced PH and the relevant mechanisms. Rats received a single intraperitoneal injection of MCT, followed by intragastric treatments with ISL (10 mg/kg/d or 30 mg/kg/d) once a day for 28 days. The MCT administration increased the right ventricular systolic pressure (RVSP) ( p < 0.001), the median width of pulmonary arteries ( p < 0.01), and the weight ratio of the right ventricular wall/left ventricular wall plus septum (Fulton index) ( p < 0.01) in rats; however, these changes were inhibited by both doses of ISL ( p < 0.05). In addition, treatment with ISL suppressed the upregulated production of serum interleukin-6 ( p < 0.01) and tumor necrosis factor- α ( p < 0.05) by MCT and reversed the increases in the numbers of proliferating cell nuclear antigen (PCNA)-positive cells ( p < 0.01) in the medial wall of pulmonary arteries. In in vitro experiments, ISL (10 μ M, 30 μ M, and 100 μ M) inhibited excessive proliferation of cultured primary pulmonary artery smooth muscle cells (PASMCs) ( p < 0.05, p < 0.01, and p < 0.001) in a dose-dependent manner and prevented an increase in the expressions of PCNA ( p < 0.01) and phospho-Akt ( p < 0.05) in PASMCs induced by hypoxia. These results suggest that ISL can attenuate MCT-induced PH via its anti-inflammatory and antiproliferative actions.